Household income dynamics in rural China - Jyotsna Jalan; Martin Ravallion (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
It is well known in theory that certain forms of non-linear dynamics in household incomes can yield poverty traps and distribution-dependent growth. The potential implications for policy are dramatic: effective social protection from transient poverty will be an investment with lasting benefits, and pro-poor redistribution will promote aggregate economic growth. We test for non-linearity in the dynamics of household expenditures and incomes using panel data for rural south-west China. While we find evidence of non-linearity, there is no sign of a dynamic poverty trap. Existing private and social arrangements in this setting appear to protect vulnerable households from the risk of destitution. However, the concavity we find in the recursion diagram does imply that the speed of recovery from an income shock is lower for the poor, and that current inequality reduces growth in mean incomes.
Keywords: C23; I32; O15; Q12; 330; income dynamics; poverty; multiple equilibria; China; Haushaltseinkommen; Verbraucherausgaben; Ländliche Armut; Ländlicher Raum; Haushaltsbudget-Statistik; China